KEPUASAN MAHASISWA TERHADAP PERPUSTAKAAN UNIVERSITAS BHAYANGKARA JAKARTA RAYA MENGGUNAKAN METODE UJI PRASYARAT BERBASIS SOFTWARE SPSS - Ahmad Bayu Bahruldin Ulum; Gilang Adel Kuswara, Muhammad Aditya, Muhammad Zaidan F, Hidayat, Fahri Baihaqi, Iskandar Zulkarnaen (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
In this Statistical Analysis Prerequisite Test research was carried out because we wanted to know student satisfaction with the facilities provided by the library. This research identifies the main factors that influence the level of student satisfaction with library services, such as physical facilities, book collections, reference services, availability of information technology, and ease of access to information. This research methodology uses a quantitative approach through a survey of a sample of students. This research aims to enable students to know what prerequisite tests are, know their function and purpose, and be able to carry out prerequisite tests. The results of this research are that many students are satisfied with the library facilities, which can be seen from the questionnaire graph and the results of the normality test, homogeneity test and linearity test. It is hoped that this research will provide valuable insight for library managers to improve their services and facilities in accordance with student expectations and needs, as well as to develop more effective strategies in increasing library user satisfaction in the future.